Single Nucleotide Polymorphisms Methods and Protocols - Kwok, Pui-Yan.; Kwok, Pui-Yan. (Methods in Molecular Biology,, 2003)
Single nucleotide polymorphisms (SNPs) have become the markers of choice in elucidating the relationship between DNA sequence variation and susceptibility to disease and have clearly become the focus of the next phase of the human genome project. In Single Nucleotide Polymorphisms: Methods and Protocols, Pui-Yan Kwok, MD, PhD, has assembled a collection of robust techniques for the difficult process of SNP discovery and genotyping. These cutting-edge protocols for mutation/SNP detection utilize denaturing high-performance liquid chromatography (dHPLC), single-strand conformation polymorphism (SSCP), conformation-sensitive gel electrophoresis (CSGE), chemical cleavage, and direct sequencing. Equally powerful and up-to-date methods are given for genotyping SNPs, including molecular beacons, the Taqman assay, single-base extension approaches, pyrosequencing, ligation, the Invader assay, and primer extension with mass spectrometry detection. Described in step-by-step detail by their inventors, each method provides extensive notes on the technical steps critical for experimental success, time-saving techniques, and tips on avoiding pitfalls. Comprehensive and authoritative, Single Nucleotide Polymorphisms: Methods and Protocols provides in a readily reproducible format all the major SNP discovery and genotyping techniques in use today, whether for using DNA diagnostics to identify a pathogen, for studying the genetic basis of human disease, or for molecular breeding programs in agriculture.